REALITAS DINAMIKA PSIKOLOGI REMAJA DAN PERMASALAHANYA PERSEPEKTIF AL-QUR’AN - suyanti ti; Yulia Tutik Nurfia; Saptono Hadi (Universitas Nahdlatul Ulama Blitar, 2022)
This descriptive qualitative research applies analytic and didactic theory approaches. In an effort to comprehend and interpret the material, descriptive observation techniques are used, and linguistic data from the textual analysis are collected for a documentary. Adolescents are assets of religion, nation, and state both in their roles as individuals and as members of society and citizens. Comprehensive self-development in all facets of life, both physically and psychologically, is required for education. From a psychological perspective, maturity is initially described as an extension of the self, characterized by a person's capacity to see other people or things as themselves, less egoism, increasing capacity for love of others and the natural world, tolerance, and the growth of an ideal ego. Second, the ability to see oneself objectively (self-objectification) means the ability to have insight into oneself, and the ability to perceive humor. And third, there is to have a certain philosophy of life (unifying philosophy of life), namely in which a person understands how he should behave in society.